Intervenção e identificação precoce do Transtorno do Desenvolvimento da Coordenação em escolares no início da alfabetização - Okuda, Paola Matiko Martins [UNESP] (2015)
The present research was developed into three studies: Study 1, aiming the development of a Motor Intervention Program based on the Response to Intervention Model, comprising students at risk for Developmental Coordination Disorder (DCD), at the beginning of literacy. The Motor Intervention Program was developed in 8 intervention sessions comprising activities with increasing complexity and motor skills, which were added from the second session, and also a Motor Observation Questionnaire, unique for all sessions. After elaboration of the program, the applicability study was conducted, as part of Study 2. Study 2, aimed to verify the applicability of the Motor Intervention Program (MIP), in students at risk for DCD, and the identification of students with DCD after the employment of MIP, prepared in study 1. A total of 89 students from the 1st grade of elementary school, from two public schools, both genders, aged between 6 years and 6 years and 8 months, took part. This study consisted of pre-testing, intervention and post-testing. All students were assessed with the Movement Assessment Battery for Children, second edition - MABC-2, in situation of pre and post-testing. The students who obtained percentile 5 (severe motor disorders), and percentile between 6 and 15 (moderate motor alterations), in the total score of the test were considered at risk for DCD. In the pre-intervention, the students were divided into two groups: Group I (GI), intervention group, with 16 students at risk for DCD, and Group II (GII), without intervention, with 73 students without motor changes. The results showed that there was applicability to both MIP and to Motor Observation Questionnaire. Group GII obtained performance superior than GI in pre- and post-intervention; the performance of GI was statistically significant after the intervention, reducing the prevalence of children at risk from 17.9% to 6.7% and thus it was possible to verify that MIP helped in ...